The Relation of Parity and Motivation With Post-Placental IUD Selection - Dinengsih, Sri; Rosyani, Rosyani (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The research aims to knowing the relationship between parity and motivation with post-placental IUD selection in West Java. This research is a qualitative study using a cross-sectional approach with total sampling. Analysis of the results is conducted by calculating the frequency distribution and bivariate analysis with the chi-square test. Result: The result shows that 68.2% who did not choose a Post Placenta IUD were mothers with primiparous parity while 53.8% of Post Placenta IUD voters were mothers with multiparous parity, mothers who did not chose a Post-Placental IUD had low motivation of 76.0% and 65, 2% of mothers with high motivation choose a post Placenta IUD, so there is a relationship between motivation and the selection of a Post-Placental IUD with a p value of 0.010. There is no relationship between parity and post-placental IUD selection. There are other variables that are related including post-placental IUD care concerns and knowledge